Paulo Freire's View on Freedom to Learn Policy - Nadlir, Nadlir; Zamzami, Muhammad Rifqi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The concept of freedom to learn is in line with the philosophy of humanism, which prioritizes human values and believes that humans have the right and freedom to think and act in whatever way they choose. Paulo Freire is a figure who initiated humanist education, which is famous for its liberating education concept. The educational philosophy of humanism and freedom to learn made by the Minister of Education and Culture has comfort. The purpose of this study is to present Paulo Freire's views on the concept of freedom to learn and the relevance of Paulo Freire's views on humanist philosophy to the concept of freedom to learn from the Ministry of Education and Culture. The article uses qualitative and descriptive research. A literature review is used to collect data, which comes from the scientific literature that is relevant to the research subject. The study produced the idea of freedom to learn as well as a humanist philosophy that emphasizes the freedom, independence, and adaptability of an educational institution in determining student needs. As learning subjects and controls, students play an important role in education. As a fundamental model for arousing student interest and cultivating a positive learning environment, this idea provides freedom, hands-on experience, creativity, and positive attitudes and perceptions.